Differential Diagnosis Clinical Presentation and Minimal Risk Factors – ST Segment Elevation Myocardial Infarction vs Myopericarditis: A Case Report - Karunia Esa, Putu Devara; Parwata Jaya, I Putu (Asian Journal of Social and Humanities, 2024)
The condition of STEMI (ST Segment Elevation Myocardial Infarction) can resemble infectious diseases of the heart such as Myopericarditis with the presence of dominant gastrointestinal symptoms, minimal demographic characteristics and cardiovascular risk factors as well as limited supporting examinations, making it a challenge in determining the diagnosis of cardiovascular disease. Case Report: 31 year old male with complaints of pain in the pit of the stomach that was difficult to describe and discomfort that extended to the chest that was not specific, a history of fever for 2 days, nausea and vomiting and a history of the habit of only consuming alcohol without smoking and the patient doing routine physical activities. ECG examination showed sinus rhythm with ST segment elevation in the precordial (anterior and lateral), inferior and LAD (Left Axis Deviation) leads as well as PR segment depression, Troponin I increased and Echocardiography showed a hypokinetic pattern in the posterior and septal segments of the heart. Fibrinolytics improved the patient's symptoms but not serial EKGs, giving rise to suspicion of STEMI which resembles Myopericarditis. Conclusion: Differential diagnosis with the possibility of myopericarditis was based on clinical findings and minimal risk factors, history of the course of the disease, ECG examination, Cardiac Biomarkers, TTE and Coronary Angiography. The patient underwent a Coronary Angiography examination with normal results, thereby ruling out a diagnosis of STEMI. The diagnostic overlap between STEMI and Myopericarditis was difficult to evaluate.